Penanaman pendidikan moral agama dan nilai-nilai budaya bangsa pada siswa di Islamic Boarding School MAN 1 Kabupaten Semarang - Mandala, Gerry; Muhlisin, Muzdakir (Journal of Smart Education and Learning, 2024)
This study aims to describe religious moral education and national cultural character at the Islamic Boarding School MAN 1 Semarang Regency, as well as supporting and inhibiting factors in its implementation. This study uses a qualitative descriptive method through field observation, interviews, and documentation. Primary data sources were obtained from the head of the boarding school, the coordinator of caregivers, and students, while secondary data were used as supporting data. The results of the study indicate that religious moral education at this boarding school includes activities to recite the Ta'lim Muta'alim book and mentoring, such as congregational prayer and sermons with a habituation method. Meanwhile, national cultural character education involves disciplinary mentoring, with a focus on religious behavior, tolerance, respect, politeness, social care, and responsibility. Supporting factors for moral education include 24-hour caregiver assistance, as well as a conducive environment. However, some students still lack self-awareness. Supporting factors for national cultural character education include the environment and educators, while the obstacles are the indifferent attitudes of some students.